2013
DOI: 10.1021/nl4021842
|View full text |Cite
|
Sign up to set email alerts
|

Snapshots of Dirac Fermions near the Dirac Point in Topological Insulators

Abstract: The recent focus on topological insulators is due to the scientific interest in the new state of quantum matter as well as the technology potential for a new generation of THz optoelectronics, spintronics and quantum computations. It is important to elucidate the dynamics of the Dirac fermions in the topologically protected surface state. Hence we utilized a novel ultrafast optical pump mid-infrared probe to explore the dynamics of Dirac fermions near the Dirac point. The femtosecond snapshots of the relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 33 publications
4
42
0
Order By: Relevance
“…The abrupt decrease in τ 1,0 at 90 K, i.e., the relaxation of QPs becoming efficient, probably indicates that an increased density of states is involved in the relaxation processes along k x . 43,44 In this scenario, the results of Fig. 3a, c also imply that the reconstruction of FS at the M point occurs mainly near 90 K, with no significant fluctuation of electronic nematicity at the M point above 100 K. As ultrafast spectroscopy is a bulk probe, the present results provide bulk evidence to support the electronic structure according to the surface-sensitive ARPES.…”
Section: Resultssupporting
confidence: 70%
“…The abrupt decrease in τ 1,0 at 90 K, i.e., the relaxation of QPs becoming efficient, probably indicates that an increased density of states is involved in the relaxation processes along k x . 43,44 In this scenario, the results of Fig. 3a, c also imply that the reconstruction of FS at the M point occurs mainly near 90 K, with no significant fluctuation of electronic nematicity at the M point above 100 K. As ultrafast spectroscopy is a bulk probe, the present results provide bulk evidence to support the electronic structure according to the surface-sensitive ARPES.…”
Section: Resultssupporting
confidence: 70%
“…Numerous prior investigations have indeed shown that the electron density in the TSS rises via transition from the bulk to the TSS [16,21,[29][30][31][32][33][34]. In our case, the time scale of this transition is about 1 ps (see again the upper and middle panels of Fig.…”
Section: Ultrafast Fano Quantum-interference Dynamicssupporting
confidence: 71%
“…In parallel with material efforts to obtain more bulkinsulating samples so that the bulk contribution to the conductivity can be completely suppressed [13][14][15], recent time-resolved (tr) experiments without spin resolution so far revealed the critical role of bulk-mediated electron-phonon scattering in the decay process of hot electrons across the linear energy-momentum dispersion of TSSs [16][17][18][19][20][21][22][23][24]. These findings indicate promising routes to overcome the problem of the bulk conductivity on ultrafast time scales, for example by generating low-energy excitations using fs-laser pulses, so that only electrons transiently occupying the TSS are excited within the bulk band gap [25].…”
Section: Introductionmentioning
confidence: 99%